2005
DOI: 10.5551/jat.12.169
|View full text |Cite
|
Sign up to set email alerts
|

CLOCK/BMAL1 is Involved in Lipid Metabolism via Transactivation of the Peroxisome Proliferator-activated Receptor (PPAR) Response Element

Abstract: Lipid absorption and metabolism are regulated by feeding and by the circadian system. It has been suggested that the expression of enzymes involved in lipid metabolism is directly controlled by the clock system. This study was designed to examine whether or not the CLOCK/BMAL1 heterodimer has transcriptional activity for genes via the peroxisome proliferator-activated receptor response element (PPRE).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(76 citation statements)
references
References 29 publications
2
73
0
1
Order By: Relevance
“…Our own and other laboratories have demonstrated that liver-type (L-FABP) and intestine-type (I-FABP) fatty acid-binding proteins, which are proteins mediating fatty acid absorption from lumen to enterocyte, are induced by dietary fat in adult rats (19,20,22,30). Additionally, previous studies have demonstrated that the gene expression of cellular retinol binding protein (CRBPII), which is a protein allowing absorption of retinol from lumen to enterocyte, is up-regulated by dietary fat (21,22,25,(31)(32)(33). Recent studies have shown that these genes, including L-FABP and CRBPII, possess a direct repeat with one space (DR-1) of AGGTCA-like motifs in their promoter regions (11, 34, …”
Section: Discussionmentioning
confidence: 99%
“…Our own and other laboratories have demonstrated that liver-type (L-FABP) and intestine-type (I-FABP) fatty acid-binding proteins, which are proteins mediating fatty acid absorption from lumen to enterocyte, are induced by dietary fat in adult rats (19,20,22,30). Additionally, previous studies have demonstrated that the gene expression of cellular retinol binding protein (CRBPII), which is a protein allowing absorption of retinol from lumen to enterocyte, is up-regulated by dietary fat (21,22,25,(31)(32)(33). Recent studies have shown that these genes, including L-FABP and CRBPII, possess a direct repeat with one space (DR-1) of AGGTCA-like motifs in their promoter regions (11, 34, …”
Section: Discussionmentioning
confidence: 99%
“…In skeletal muscle, RORα regulates lipid homeostasis via direct activation of carnitine palmitoyltransferase 1 (`mqN), involved in fatty acid oxidation, and caveolin-3 (Lau et al, 2004). Rhythmic transcriptional activation by CLOCK/BMAL1 is a key regulator of lipid metabolic enzymes such as acyl-CoA oxidase (^lu), 3-hydroxy-3-methylglutaryl coenzyme A (ejdJ`ç^) synthase (eãÖÅëN) and cellular retinol binding protein II (`o_m=ff) (Inoue= et alK, 2005).…”
Section: Circadian Control Of Metabolismmentioning
confidence: 99%
“…Both the PPARα transcript and protein oscillate in mouse liver with a time of peak expression consistent with regulation by local circadian clocks (Lemberger et al 1996). Pparα transcription can be directly regulated by CLOCK and BMAL1 in vitro and in the liver and intestine in vivo (Inoue et al 2005;Oishi et al 2005;Canaple et al 2006). As discussed above, the endogenous PPARα ligand OEA is synthesized diurnally in the gut epithelium, probably in response to nutrient availability.…”
Section: Pparsmentioning
confidence: 99%